2000
DOI: 10.1111/j.1365-2621.2000.tb15997.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Loss and Lipid Oxidation for Precooked Beef Patties Stored in Edible Coatings and Films

Abstract: Edible/biodegradable wheat gluten (WG), soy protein (SP), carrageenan (CA) and chitosan (CH) films and coatings were used on precooked beef patties. After 3 d of refrigerated storage, no difference was found in moisture loss between WG, SP, and CH film-wrapped patties and unpackaged patties (control-A). All coatings were as effective as polyvinyl chloride film (control-B) in reducing moisture loss. CA film decreased moisture loss but not as effective as control-B. WG, SP, and CA coatings and CA film reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 31 publications
12
40
2
1
Order By: Relevance
“…The SPI-coated samples had the less amount of moisture loss. A previous report indicated that soy protein coating effectively reduced the moisture loss in precooked beef patties [Wu et al, 2000]. Mixing of CMC with the SPI in the coating mixture resulted in significant improvement of the PML value by 20.5, 17.4 and 12.8% for apple, potato and carrot, respectively (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The SPI-coated samples had the less amount of moisture loss. A previous report indicated that soy protein coating effectively reduced the moisture loss in precooked beef patties [Wu et al, 2000]. Mixing of CMC with the SPI in the coating mixture resulted in significant improvement of the PML value by 20.5, 17.4 and 12.8% for apple, potato and carrot, respectively (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…However, coated patties maintained initial moisture contents under each storage period. Wu et al (2000) reported no signiWcant diVerences in moisture loss between gluten, soy protein and chitosan wrapped patties and unpackaged patties after 3 days of refrigeration. Similarly, Dong, Cheng, Tan, Zheng, and Jiang (2004) reported chitosan coating of peeled litchi fruit retarded weight loss.…”
Section: Moisture Contentmentioning
confidence: 93%
“…Eyas (2001) indicated that the diminished juiciness might be due to the loss of moisture from the products during storage as low-density polyethylene packages were permeable to moisture. The gradual decrease in textural scores might be due to release of moisture (Wu et al 2000) and depletion of fat during storage (Biswas 2002). Jay (1996) reported that it might be due to the breakdown of muscle fibre protein by bacterial action resulting in decreased water binding capacity.…”
Section: Sensory Evaluationmentioning
confidence: 99%